2D boron nitride nanoflakes as a multifunctional additive in gel polymer electrolytes for safe, long cycle life and high rate lithium metal batteries. Issue 9 (12th June 2017) - Shim, Jimin; Kim, Hee Joong; Kim, Byoung Gak; Kim, Yong Seok; Kim, Dong-Gyun; Lee, Jong-Chan
Abstract : Highly dendrite-suppressing gel polymer electrolytes for lithium metal batteries are presented utilizing perfluoropolyether-functionalized 2D boron nitride nanoflakes as a multifunctional additive. Abstract : The multifunctional properties of 2D boron nitride nanoflakes (BNNFs) in gel polymer electrolytes (GPEs) are presented. A small addition (0.5 wt%) of BNNFs into the GPE substantially improves all the advantageous properties of the GPE including ionic conductivity, Li + transference number, mechanical modulus, and dendrite-suppressing capability, thereby enabling high performance lithium metal batteries.